2014
DOI: 10.1007/s13204-014-0336-z
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer studies of the synthesized gold nanoparticles against MCF 7 breast cancer cell lines

Abstract: It has been previously stated that gold nanoparticles have been successfully synthesized using various green extracts of plants. The synthesized gold nanoparticles were characterized under scanning electron microscopy and EDX to identify the size of the nanoparticles. It was found that the nanoparticles were around 30 nm in size, which is a commendable nano dimension achieved through a plant mediated synthesis. The nanoparticles were further studied for their various applications. In the current study, we have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(8 citation statements)
references
References 4 publications
2
6
0
Order By: Relevance
“…Previous studies have also reported the antiproliferative potential of AuNPs in colon, 22 breast, 33 cholangiocarcinoma, 34 cervical, and ovarian 35 cancer cell lines and our current results are consistent with the above studies. Further, green synthesis of AuNPs using plants proved to be efficient even at 2 μg/mL inhibits the proliferation of breast cancer cells 33 . These studies show that regardless of the mode of synthesis (chemical, phyto, and microbial), AuNPs have the potential to inhibit the proliferation of cancer cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous studies have also reported the antiproliferative potential of AuNPs in colon, 22 breast, 33 cholangiocarcinoma, 34 cervical, and ovarian 35 cancer cell lines and our current results are consistent with the above studies. Further, green synthesis of AuNPs using plants proved to be efficient even at 2 μg/mL inhibits the proliferation of breast cancer cells 33 . These studies show that regardless of the mode of synthesis (chemical, phyto, and microbial), AuNPs have the potential to inhibit the proliferation of cancer cells.…”
Section: Discussionsupporting
confidence: 93%
“…AuNPs smaller than 10 nm have effectively entered and accumulated in tumors cells and thereby induced cell death 4,32 . Previous studies have also reported the antiproliferative potential of AuNPs in colon, 22 breast, 33 cholangiocarcinoma, 34 cervical, and ovarian 35 cancer cell lines and our current results are consistent with the above studies. Further, green synthesis of AuNPs using plants proved to be efficient even at 2 μg/mL inhibits the proliferation of breast cancer cells 33 .…”
Section: Discussionsupporting
confidence: 92%
“…22 Plant based biogenic method is one of the best candidates for largescale production of nanoparticles with well-defined size and morphology. 24 A variety of biogenic AuNPs, with different therapeutic properties such as vermifugal, 25 antibacterial, 26 antifungal 27 and anticancer, 28,29 have been recently reported. 22 The combination of inherent physicochemical properties of nanoparticles with those of biomolecules could led to the development of functionalized nano-biological constructs with attracting characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Many plants (Camellia sinensis, Coriandrum sativum, Mentha arvensis, Phyl-lanthus amarus, Artabotrys hexapetalus, Mimusops elengi, Syzygium aromaticum) were described by Priya and Iyer, which showed that the green synthesized AuNPs have anticancer activity against the human breast cancer cell line, i.e., MCF7 and found that AuNPs at a minimum concentration of 2 µg/mL for cancer therapy are as effective as standard drugs. Moreover, the increase in the nanoparticle concentration is directly proportional to the effectiveness against cancer [131]. The increasing demand for biosynthesized gold nanoparticles has been greatly facilitated in medical applications, particularly in targeted drug delivery, one of the most recent advances in nanotechnology.…”
Section: Plant-based Synthesized Gold Nanoparticles As Anticancer Agentsmentioning
confidence: 99%